Zmiany w podstawowych strukturach wytwórczych w rolnictwie w gminach województwa poznańskiego po 1989 roku - Czyżewski, Andrzej; Bak, Urszula (Wydział Prawa i Administracji UAM, 1997)
The article presents results of research work on structural changes within two fundamental production resources, i.e. land and labour, in the agriculture of the Poznań province after 1989. The most spectacular and advantageous transformations occurred within the scope of property structure. The share of private sector in total area of cultivable land has considerably increased. Progress in agrarian structure has been noted. The land concentration degree within privateowned farms was relatively high. Lack of demand for rural labour force on the scale of the whole national economy has limited transformation process within the labour resource. Relatively high level of employment in agriculture is still maintained.
Transformation in fundamental agricultural production structures within communes of the Poznań province after 1989